Giving gifts a children's storybook and learning module with a culminating program with the Alternative Learning Resource School Students (ALRES) - Fajardo, Carla Louisse; Guadalupe, Jocelyn T. (Quezon City College of Music, University of the Philippines Diliman, 2018)
The project consists mainly of an original storybook with musical activities targeted for children with autism and development delays. It includes an audio CD that is used in music activities and storytelling. The story includes life values and skills such as developing good self-esteem, self-awareness, and respect for others.
Thesis (B.M. Music) -- University of the Philippines Diliman
Keywords: School music -- Instruction and study